2018
DOI: 10.1177/0023830918816351
|View full text |Cite
|
Sign up to set email alerts
|

The Prosody of Rhetorical and Information-Seeking Questions in German

Abstract: This paper reports on the prosody of rhetorical questions (RQs) and information-seeking questions (ISQs) in German for two question types—polar questions and constituent questions (henceforth “ wh-questions”). The results are as follows: Phonologically, polar RQs were mainly realized with H-% (high plateau), while polar ISQs mostly ended in H-^H% (high-rise). Wh-RQs almost exclusively terminated in a low edge tone, whereas wh-ISQs allowed for more tonal variation (L-%, L-H%, H-^H%). Irrespective of question ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
103
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(120 citation statements)
references
References 61 publications
8
103
0
9
Order By: Relevance
“…Ainda, é importante destacar que, em termos discursivos, as interrogativas podem ser divididas entre perguntas plenas e retóricas de acordo com a intenção comunicativa do falante. A pergunta plena se caracteriza por buscar informação a ser dada pelo interlocutor na forma de resposta verbal (Silva e Santos, 2015;Braun et al, 2018). Quanto à retórica, é formulada para não ser respondida (Silva e Santos, 2015) e, para Braun et al (2018), tem por objetivo buscar o engajamento do interlocutor à questão, e não uma resposta.…”
Section: Algumas Considerações Sobre As Interrogativasunclassified
See 2 more Smart Citations
“…Ainda, é importante destacar que, em termos discursivos, as interrogativas podem ser divididas entre perguntas plenas e retóricas de acordo com a intenção comunicativa do falante. A pergunta plena se caracteriza por buscar informação a ser dada pelo interlocutor na forma de resposta verbal (Silva e Santos, 2015;Braun et al, 2018). Quanto à retórica, é formulada para não ser respondida (Silva e Santos, 2015) e, para Braun et al (2018), tem por objetivo buscar o engajamento do interlocutor à questão, e não uma resposta.…”
Section: Algumas Considerações Sobre As Interrogativasunclassified
“…A pergunta plena se caracteriza por buscar informação a ser dada pelo interlocutor na forma de resposta verbal (Silva e Santos, 2015;Braun et al, 2018). Quanto à retórica, é formulada para não ser respondida (Silva e Santos, 2015) e, para Braun et al (2018), tem por objetivo buscar o engajamento do interlocutor à questão, e não uma resposta. Dehé e Braun (2019) defendem que a pergunta retórica tem três características: não espera resposta; tem a "sensação de uma afirmação" ("the feel of an assertion", Dehé e Braun, 2019, p. 2); e pode ser opcionalmente respondida.…”
Section: Algumas Considerações Sobre As Interrogativasunclassified
See 1 more Smart Citation
“…Corpus analyses have shown that rhetorical questions differ from information-seeking questions in their prosodic realization [4,5], regarding boundary tones and pitch accents. Previous experimental work in German has shown that questions in a rhetorical context differ from questions in an information-seeking context in terms of their prosodic realization [6]. RQs are more often realized with nuclear L*+H accents than ISQs, have longer constituent durations and more often a breathy voice quality, irrespective of question type (whquestion or polar question).…”
Section: Introductionmentioning
confidence: 96%
“…Longer constituent durations in RQs than in ISQs have indeed been reported for German (Braun et al . 2018) and for Icelandic (Dehé et al 2018).…”
Section: Introductionmentioning
confidence: 99%